Ahp-Cyclodepsipeptides as tunable inhibitors of human neutrophil elastase and kallikrein 7: Total synthesis of tutuilamide A, serine protease selectivity profile and comparison with lyngbyastatin 7. Issue 23 (1st December 2020) - Chen, Qi-Yin; Luo, Danmeng; Seabra, Gustavo M.; Luesch, Hendrik
Graphical abstract: Abstract: We describe the total synthesis of tutuilamide A, a potent porcine pancreatic elastase (PPE) inhibitor and a representative member of the 3-amino-6-hydroxy-2-piperidone (Ahp) cyclodepsipeptide family, isolated from marine cyanobacteria. The Ahp unit serves as a pharmacophore and the adjacent 2-amino-2-butenoic acid (Abu) is a main driver of the selectivity among serine proteases. We adapted our previous convergent strategy to generate the macrocycle, common with lyngbyastatin 7 and related elastase inhibitors, and then appended the tutuilamide A-specific side chain bearing a vinyl chloride. Tutuilamide A and lyngbyastatin 7 were evaluated side by side for the inhibition of the disease-relevant human neutrophil elastase (HNE). Tutuilamide A and lyngbyastatin 7 were approximately equipotent against HNE, while tutuilamide A was previously shown to be more active against PPE compared with lyngbyastatin 7, further demonstrating that the side chain provides opportunities to not only modulate potency but also selectivity among proteases of the same function from different organisms. Profiling of tutuilamide A against mainly human serine proteases revealed high selectivity for HNE (IC50 0.73 nM) and pleiotropic activity against kallikrein 7 (KLK7, IC50 5.0 nM), without affecting other kallikreins, similarly to lyngbyastatin 7 (IC50 0.85 nM for HNE and 3.1 nM for KLK7). A comprehensive molecular docking study for elastases and KLK7 afforded deeper insight into the intricate differences between inhibitor interactions with HNE and PPE, accounting for the differential activities for both compounds. The synthesis and molecular studies serve as a proof-of-concept that the macrocyclic scaffold can be diversified to fine-tune the activity of serine protease inhibitors.